2022
DOI: 10.1177/20406207221141511
|View full text |Cite
|
Sign up to set email alerts
|

The role of CAR-T cell therapy as second line in diffuse large B-cell lymphoma

Abstract: For approximately three decades, autologous hematopoietic cell transplantation (auto-HCT) has been the standard of care for patients with relapsed/refractory (R/R) diffuse large B-cell lymphoma (DLBCL) after frontline therapy. This approach is limited due to the intensity of chemotherapy and the proportion of patients who relapse after auto-HCT. Since the approval of anti-CD19 chimeric antigen receptor T-cell (CAR-T) therapy and novel agents, the treatment paradigm for DLBCL has changed remarkably. Anti-CD19 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…To this end, further investigation is warranted to determine if therapeutic resistance is associated with STAT6 D419 -induced microenvironmental remodeling. From a therapeutic angle, knowing how the tumor influences the surrounding immune cells is important, as cellular therapies, such as CAR-T [50,51], are being increasingly used to treat rrDLBCL. Future studies may examine if STAT6 mutations affect responses to these novel therapies, by using immunocompetent mouse models that allow for the careful dissection and manipulation of the TME.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, further investigation is warranted to determine if therapeutic resistance is associated with STAT6 D419 -induced microenvironmental remodeling. From a therapeutic angle, knowing how the tumor influences the surrounding immune cells is important, as cellular therapies, such as CAR-T [50,51], are being increasingly used to treat rrDLBCL. Future studies may examine if STAT6 mutations affect responses to these novel therapies, by using immunocompetent mouse models that allow for the careful dissection and manipulation of the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Three formulations of the chimeric antigen receptor T cell (CAR-T) therapy, axicabtagene ciloleucel, tisagenlecleucel, and lisocabtagene maraleucel, have been approved by the FDA for the treatment of relapsed/refractory DLBCL patients ( 83 ). The ZUMA-7, BELINDA, and TRANSFORM phase 3 clinical trials showed significant efficacy of CAR-Ts in the second line of treatment, and challenged the second line standard of care (SOC) with autologous stem cell transplantation.…”
Section: Zanubrutinib In Other Lymphoid Malignanciesmentioning
confidence: 99%